The ugly Japanese : - Bartu, Friedemann (Yenbooks, 1993)
As the 20th century draws to a close, Japan is establishing itself as a leading economic force in the world in general and in the Asia-Pacific region in particular. Increased Japanese involvement in Southeast Asia has fostered the region's economic development, but it has also brought the Japanese into close contact with the very different cultures of Asia, to most of which Tokyo's economic supremacy is a mixed blessing. While Japanese officials strive to find a niche for Japan to coexist peacefully with its neighbors, Japanese businesses have steamrolled Southeast Asia and turned it into a vast Japanese back garden. The region has reacted to this Japanese takeover with apprehension and anger, but many Japanese seem to ignore such concerns and therefore appear arrogant and selfish in the eyes of their neighbors. Half a century after the birth of the "ugly American" the Asia-Pacific world is clearly witnessing the rise of the "Ugly Japanese".